2012
DOI: 10.1038/srep00274
|View full text |Cite
|
Sign up to set email alerts
|

Order versus Disorder: in vivo bone formation within osteoconductive scaffolds

Abstract: In modern biomaterial design the generation of an environment mimicking some of the extracellular matrix features is envisaged to support molecular cross-talk between cells and scaffolds during tissue formation/remodeling. In bone substitutes chemical biomimesis has been particularly exploited; conversely, the relevance of pre-determined scaffold architecture for regenerated bone outputs is still unclear. Thus we aimed to demonstrate that a different organization of collagen fibers within newly formed bone und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 32 publications
1
83
0
1
Order By: Relevance
“…Furthermore, the confined porous structure of HA/TCP and PU can concentrate collagen fibers within the pores and trigger their self-assembly, thereby forming the lamellar-like bone (Scaglione et al, 2012). Conversely, in fibrous PLGA/PCL scaffolds, new collagen fibers formed by the cells were distributed in a random manner, resulting mostly in woven bone (Scaglione et al, 2012). Thus, the specific design of the scaffold can drive the arrangement of collagen fibers and consequently target bone formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the confined porous structure of HA/TCP and PU can concentrate collagen fibers within the pores and trigger their self-assembly, thereby forming the lamellar-like bone (Scaglione et al, 2012). Conversely, in fibrous PLGA/PCL scaffolds, new collagen fibers formed by the cells were distributed in a random manner, resulting mostly in woven bone (Scaglione et al, 2012). Thus, the specific design of the scaffold can drive the arrangement of collagen fibers and consequently target bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the small pore size of PLGA/PCL scaffolds might have created a hypoxic environment which favored the cartilage maintenance (Karageorgiou and Kaplan, 2005). Furthermore, the confined porous structure of HA/TCP and PU can concentrate collagen fibers within the pores and trigger their self-assembly, thereby forming the lamellar-like bone (Scaglione et al, 2012). Conversely, in fibrous PLGA/PCL scaffolds, new collagen fibers formed by the cells were distributed in a random manner, resulting mostly in woven bone (Scaglione et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The results indicated that the geometry of the interconnected porous structure creates spaces for vasculature that lead to osteogenesis, while the dense structure inhibits vascular formation and proliferation of cells, preventing bone formation (Kuboki et al, 1998). Indeed, porosity and pathways of pore interconnection have a strong impact on osteogenisis, since high porosity levels are necessary for bone matrix deposition in the empty spaces (Scaglione et al, 2012). In this regard, the use of biodegradable polymers, such as CS, associated to more-soluble forms of CP as bone substitutes allows the composite to initially support the mechanical stress and be re-absorbed over the time, opening space for new bone deposition (Penk et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Sel-sel progenitor akan menempel pada scaffold dan akan berdiferensiasi menjadi osteoblas dan memberikan tempat untuk deposisi matriks tulang serta jalur pembuluh darah sebagai suplai nutrisi. 6,18,42,43,44 Fibroblast growth factor (FGF) terbukti merangsang pertumbuhan tulang, sintesis kolagen pada bone healing baik secara in vitro maupun in vivo. 45 Dari teori tersebut dapat menjadi alasan ekspresi FGF-2 pada K(+) dengan aplikasi hidroksiapatit lebih meningkat dibandingkan dengan K(-) yang tidak diaplikasikan hidroksiapatit.…”
Section: Pembahasanunclassified